2020
DOI: 10.1038/s41467-020-15423-5
|View full text |Cite
|
Sign up to set email alerts
|

GPR56/ADGRG1 is associated with response to antidepressant treatment

Abstract: It remains unclear why many patients with depression do not respond to antidepressant treatment. In three cohorts of individuals with depression and treated with serotoninnorepinephrine reuptake inhibitor (N = 424) we show that responders, but not nonresponders, display an increase of GPR56 mRNA in the blood. In a small group of subjects we also show that GPR56 is downregulated in the PFC of individuals with depression that died by suicide. In mice, we show that chronic stress-induced Gpr56 downregulation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 41 publications
0
51
0
Order By: Relevance
“…Recent findings have shown the association of another adhesion GPCR with depression—ADGRG1 (GPR56) [ 66 ]. As described for ADGRB2, the mechanism of ADGRG1 activation involves the self-cleavage of its long ectodomain to expose a stimulating tethered ligand [ 98 , 99 ].…”
Section: Systematic Analysis Of Ogpcrs In Anxiety and Mood Disordementioning
confidence: 99%
See 1 more Smart Citation
“…Recent findings have shown the association of another adhesion GPCR with depression—ADGRG1 (GPR56) [ 66 ]. As described for ADGRB2, the mechanism of ADGRG1 activation involves the self-cleavage of its long ectodomain to expose a stimulating tethered ligand [ 98 , 99 ].…”
Section: Systematic Analysis Of Ogpcrs In Anxiety and Mood Disordementioning
confidence: 99%
“…ADGRG1 mRNA in blood cells was up-regulated in response to a variety of antidepressant treatments, but, importantly, only in patients responding to the therapy and not in respondent patients treated with placebo [ 66 ]. Remarkably, transcriptomic studies on post-mortem brain tissues from MDD patients and control subjects revealed a significant down-regulation of ADGRG1 in the dorsolateral PFC [ 59 ].…”
Section: Systematic Analysis Of Ogpcrs In Anxiety and Mood Disordementioning
confidence: 99%
“…We downloaded the gene expression profile data (series accession number: GSE146446 [26] and GSE45468 [27]) in the Gene Expression Omnibus database for using Biobase and GEOquery package in R. Both data used the GPL570 platform (Affymetrix Human Genome U133 Plus 2.0 Array; Agilent Technologies, Palo Alto, CA, USA). We found the Affymetrix probe IDs by searching for the gene name.…”
Section: Analysis Of Public Microarray Datamentioning
confidence: 99%
“…Among them, CALU represented significance for the treatment/time/response interaction term (p-value < 0.05), and CTSD and SH3BGRL3 represented significance for the treatment/response interaction term (p-value < 0.05; Figure 3B). Because we could not find a benchmark study on blood protein-based drug responsiveness to antidepressants, we examined the expression patterns of LMM-significant 37 proteins described in the results of large-scale studies at the blood circulating cell-free mRNA level from two publicly available GEO datasets-(GSE146446 [26] and GSE45468 [27]). Unlike the proteomic study above, the two GEO studies contained results on the effects of patients receiving a placebo.…”
Section: External Validation In Public Studies Of Mrna Expressionmentioning
confidence: 99%
“…GPR56/ADGRG1 belongs to the aGPCR family and plays a critical role in diverse pathophysiological processes such as brain development 12,[23][24][25][26][27] , major depressive disorder 28 , peripheral immunity 29,30 , CNS immunity 31 , skeletal muscle development [32][33][34] , pancreatic beta-cell function 35,36 , and cancer progression [37][38][39][40][41][42][43] . We have shown that the GPR56 ECR is composed of an N-terminal pentraxin and laminin/neurexin/sex hormone-binding globulin (PLL) domain and a juxtamembrane GPCR autoproteolysis-inducing (GAIN) domain and that the ECR plays a receptor-autonomous regulatory role in G protein signaling 12 .…”
mentioning
confidence: 99%